Balancing breadth and depth of expertise for innovation : a 3M story - Boh, Wai Fong (2013)
This study examines how inventors’ breadth and depth of expertise influence innovation in 3M, a company renowned for sustained innovation for over a century. While prior research tends to examine a single indicator – the technical success achieved by the inventor – our study differentiates between three indicators of a successful inventor: (1) the number of inventions generated; (2) the extent to which the inventor has a significant impact in his or her technical domain; and (3) the inventor's career success, in terms of the commercial value they have brought by converting their inventions into products that generate sales for commercial organizations. We found that breadth of inventor expertise relates to the generation of many inventions, but not necessarily to those that are technically influential. Depth of inventor expertise enables individuals to generate technically influential inventions, as measured by patents granted. However, both breadth and depth of expertise are required for innovators to be deemed highly valuable, based on their records of effectively converting inventions into commercially successful products. Our study extends prior research on innovation in two ways. We provide a comprehensive view of how inventors’ expertise influences innovation and also show how inventors with different expertise profiles can contribute in unique ways to their organization.